2017
DOI: 10.1007/978-3-319-49719-8_2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Methods for the Study of Hydrodynamic Cavitation

Abstract: A review of traditional and novel experimental methods for the investigation of hydrodynamic cavitation is presented. The importance of water quality is discussed, along with its characterization and management. Methods for the direct and indirect experimental determination of cavitation inception are presented. Along with traditional optical visualization, methods of measuring developed cavitation are described, including point and surface electrical probes, optical bubble probes, acoustic measurements, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Several studies have described cavitation noise: for example, a tip vortex was reported as a “singing vortex” because of the cavitation noise or the cavitation noise from an orifice was described as pebbles being rolled through the device . A hydrophone type of instrument is commonly used for the acquisition of noise. , Hydrophones are especially useful for underwater acquisition given the requirement of acquisition in propellers and turbines . Different data processing techniques on the time and frequency spectra are used to analyze the cavitation noise: for example, the counting of number of peaks larger than certain threshold and fast Fourier transform spectra , ,, are used to identify the inception condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have described cavitation noise: for example, a tip vortex was reported as a “singing vortex” because of the cavitation noise or the cavitation noise from an orifice was described as pebbles being rolled through the device . A hydrophone type of instrument is commonly used for the acquisition of noise. , Hydrophones are especially useful for underwater acquisition given the requirement of acquisition in propellers and turbines . Different data processing techniques on the time and frequency spectra are used to analyze the cavitation noise: for example, the counting of number of peaks larger than certain threshold and fast Fourier transform spectra , ,, are used to identify the inception condition.…”
Section: Introductionmentioning
confidence: 99%
“…24 A hydrophone type of instrument is commonly used for the acquisition of noise. 19,25 Hydrophones are especially useful for underwater acquisition given the requirement of acquisition in propellers and turbines. 20 Different data processing techniques on the time and frequency spectra are used to analyze the cavitation noise: for example, the counting of number of peaks larger than certain threshold 26−28 and fast Fourier transform spectra 7,20 −22,29,30 are used to identify the inception condition.…”
Section: Introductionmentioning
confidence: 99%